AB0681 COMPARISON BETWEEN DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF PREDOMINANT AXIAL VS MAINLY PERIPHERAL SPONDYLOARTHRITIS (SpA) PATIENTS, ENROLLED IN THE ONGOING SIRENA STUDY. (2nd June 2020) - Foti, R.; Cardinale, G.; Costa, L.; Franceschini, F.; Ciccia, F.; Marchesoni, A.; Guggino, G.; Rossini, M.; Lubrano, E.; Galeazzi, M.; Chimenti, M.; Bianchi, G.; et al.
Abstract : Background: SIRENA is an Italian, prospective Registry in Spondyloarthritis (SpA) patients, naïve to conventional, targeted and biological DMARDs. Patients are diagnosed, newly or confirmed, according to ASAS criteria and classified in subjects with predominant axial (AX ) or with mainly peripheral manifestations (PER ). Objectives: To compare descriptively AX vs PER subgroups of patients. Methods: Demographic data, diagnostic delay and subtypes of SpA as well as clinical features and comorbidities are collected. Results: 282 patients were enrolled: 101 (35.8%) AX and 181 (64.2%) PER. Baseline data are shown in Table 1. There were more obese patients in AX (21.4% AX vs 16.1% PER) and more overweight ones in PER (19.4% AX vs 23.8% PER). The % of subjects with diagnostic delay was higher in AX (65.7% vs 53.9% PER) and the delay longer (mean of 73.1 months vs 47.8). In both groups, main reason of the delay was incorrect referrals (41.5% for AX and 45.3% for PER). Noteworthy the fact that in PER, the 75.7% of patients had a newly diagnosed SpA. In PER, the most frequent SpA type was PsA (82.3%), followed by undifferentiated SpA (8.8%) and enteropathic SpA (7.5%), while in AX, 49.5% were ankylosing spondylitis, 21.8% nr-ax-SpA and only 4% PsA. The majority of PER patients reported as first symptom peripheral arthritis (80/181), psoriasis (57/181) and enthesitis while in AX referred inflammatory back pain (80/101). High percentages of comorbidities were reported: psoriasis (65.8%) and cardiometabolic diseases (34.8%) were higher in PER while depression/anxiety and GI diseases were higher in AX (Table 2). At the baseline, the mean PhGA score (0-100) was 51.5 for AX and 43.8 for PER. Conclusion: SIRENA study highlights relevant differences in AX vs PER patients, expecially in terms of diagnostic delay, clinical presentation and comorbidities. Acknowledgments: This study was sponsored by Janssen Italy. We thank the Investigators and their staff at all of the study sites. Disclosure of Interests: Rosario Foti Speakers bureau: Abbvie, BMS, ROCHE, Janssen, Celgene, Gabriella Cardinale: None declared, Luisa Costa: None declared, Franco Franceschini Consultant of: Eli-Lilly, Janssen, Pfizer, Sanofi-Genzyme, UCB Pharma, GSK, Francesco Ciccia Grant/research support from: Pfizer, Novartis, Celgene, Janssen, Consultant of: Lilly, Novartis, Pfizer, Janssen, Roche, Celgene, Speakers bureau: Pfizer, Novartis, Celgene, Janssen, Roche, Abiogen, BMS, Antonio Marchesoni Speakers bureau: Abbvie, Pfizer, UCB, Novartis, Celgene, Eli Lilly, Giuliana Guggino Grant/research support from: Pfizer, Celgene, Speakers bureau: Celgene, Sandoz, Pfizer, Maurizio Rossini Speakers bureau: AbbVie, Abiogen, Amgen, BMS, Eli-Lilly, Novartis, Pfizer, Sanofi, Sandoz and UCB, Ennio Lubrano: None declared, Mauro Galeazzi: None declared, Mariasole Chimenti: None declared, Gerolamo Bianchi Grant/research support from: Celgene, Consultant of: Amgen, Janssen, Merck Sharp & Dohme, Novartis, UCB, Speakers bureau: Abbvie, Abiogen, Alfa-Sigma, Amgen, BMS, Celgene, Chiesi, Eli Lilly, GSK, Janssen, Medac, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Sanofi Genzyme, Servier, UCB, Giuseppe Galfo: None declared, Silvia Marelli Employee of: Janssen, Ennio Favalli Speakers bureau: BMS, Eli-Lilly, MSD, UCB, Pfizer, Sanofi-Genzyme, Novartis and Abbvie